CircRtn4 Acts as the Sponge of miR-24-3p to Promote Neurite Growth by Regulating CHD5 - Qi, Yue; Ma, Nana; Chen, Xiaofan; Wang, Yue; Zhang, Wei; Wan, Jun (Frontiers in Molecular Neuroscience, 2021)
Circular RNAs (circRNAs) are covalently closed single-stranded RNA molecules. After derived from precursor mRNA back-splicing, circRNAs play important roles in many biological processes. Recently, it was shown that several circRNAs were enriched in the mammalian brain with unclear functions. The expression of circRtn4 in the mouse brain was increased with the differentiation of primary neurons. In our study, knockdown of circRtn4 inhibited neurite growth, while overexpression of circRtn4 significantly increased neurite length. By dual-luciferase reporter assay and RNA antisense purification assay, circRtn4 was identified as a miRNA sponge for miR-24-3p. Moreover, knockdown of miR-24-3p increased neurite length, while overexpression of miR-24-3p significantly inhibited neurite growth. Furthermore, CHD5 was confirmed to be a downstream target gene of miR-24-3p. And CHD5 silence counteracted the positive effect of circRtn4 overexpression on neurite growth. In conclusion, circRtn4 may act as the sponge for miR-24-3p to promote neurite growth by regulating CHD5.